Caracterização pós-colheita de propriedades físicas e químicas de morangos produzidos sob diferentes sistemas de cultivo. - Almeida, Maria Lucilania Bezerra (2013)
The strawberry can be grown in different conditions of climate and soil. The incorporation of new technologies, in order to raising the productivity of this crop has been used with some frequency, especially using the system of semi-hydroponic cultivation. These technological incorporations affect not only productivity but also quality of fruits in both pre-and post-harvest. Fruit quality is of great importance when studying the behavior of cultivars in a given region. It allows more precise information about some of the main characteristics of the final product like as the sensory properties (appearance, texture, flavor and fragrance), the nutritive value and its ability to be used as a multifunctional product. Therefore, this study aimed to characterize post-harvest chemical and physical properties of strawberries grown under different cropping systems. The research was conducted on a property located in Ibiapina, CE. The experiment was conducted in a 3x4 factorial, by three cropping systems (semi-hydroponic - troughs and pad - and conventional) and four cultivars of strawberry (Oso Grande Festival, Camarosa and Albion). After harvest the fruits were brought to the Laboratory of Physiology and Post-Harvest Technology of Embrapa Agroindústria in Fortaleza, CE, Brazil, where they were analyzed in relation to the average mass, firmness of the pulp, length, diameter, titratable acidity, pH, total soluble solids, SS/TA ratio, total sugars, vitamin C, total extractable polyphenols and total antioxidant activity. It was observed a strawberry production of high-quality in the city of Ibiapina, CE. The trough system plus cv. Oso Grande showed the best result for obtaining a larger fruit. The best result for the firmness and physicochemical variables was observed in the conventional system with the cv. Albion.